Orientation towards the vernacular and style-shifting as language behaviours in speech of first-generation Polish migrant communities speaking Norwegian in Norway - Malarski, Kamil; Castle, Chloe; Awedyk, Witosław; Wrembel, Magdalena; Jensen, Isabel Nadine (Frontiers in Psychology, 2024)
This study describes the patterns of dialect use among L3 Norwegian speakers born in Poland who have migrated to Norway. We collected the data in the form of sociolinguistic interviews recorded in Tromsø and Oslo, two different dialect regions, in order to examine potential differences in acquisition of two dissimilar dialects in Norwegian by L3 speakers. The analyses focus on dialectal and accentual variation in their speech, and whether frequency of dialect use is dependent on selected sociocultural factors. We have found that some speakers, especially those scoring high for overall dialect use, also display style-shifting, i.e. they use dialect features from the region more frequently in unscripted speech as opposed to in more formal speech styles elicited through reading tasks or the wordlist reading tasks. This demonstrates that language learners are capable of developing sensitivity towards the vernacular form in an L3. Moreover, it shows that first-generation migrant communities in fact may be capable of developing their L2/L3/L4 language competencies in a similar way to L1 speakers, including at the level of sociolinguistic variation.